Paediatric dental trauma: insights from epidemiological studies and management recommendations - Alessandra Laforgia; Angelo Michele Inchingolo; Francesco Inchingolo; Roberta Sardano; Irma Trilli; Angela Di Noia; Laura Ferrante; Andrea Palermo; Alessio Danilo Inchingolo; Gianna Dipalma (BMC Oral Health)
Abstract Dental trauma is common in all age groups, although, epidemiologically, it is more common in children with studies that indicate that 15% of preschoolers and 20–25% of school-age children experience it. These injuries, which frequently call for immediate attention, can affect the hard tissues and supporting components of the teeth, and, because dental damage in deciduous teeth occurs frequently and affects speech, nutrition, and oral development, it is particularly worrying. After searching three databases, Scopus, Web of Science (WoS), and PubMed, and removing duplicates, 3,630 articles were screened, and 12 publications were included in the qualitative analysis. Due to their busy lifestyles, children are particularly susceptible to oral trauma and in certain areas and lower socioeconomic groups, the incidence is higher. From little fractures in the enamel to serious dislocations and avulsions, injuries vary and must be treated promptly in order to avoid consequences and to prevent long-term issues. Furthermore, a conservative treatment strategy is recommended to preserve tooth vitality and prevent extractions. Reducing the occurrence of dental injuries requires the implementation of preventive measures including mouthguard use and educational campaigns. In summary, this review emphasizes the importance of early diagnosis, immediate management, and long-term care, by synthesizing existing knowledge on the prevalence, types, management, complications, and prevention of dental trauma in deciduous teeth. Finally, it’s important to underscore the need for continued research to refine treatment approaches.